Mengamati Perkembangan Anak Usia 7 Tahun Melalui Kunjungan ke Rumah - Lubis, Ramadhan; Amelia, Flora; Handayani, Fitri; Munawwarah, Najwatul; N, Nurlailiana; Dirda, Sheltiva Fhazahra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Development of Children Aged 7-8 Years Through Direct Visits This study aims to observe the development of children aged 7-8 years through direct visits to their homes. The focus of the study includes children’s cognitive, emotional, spiritual, and motor development. The research method uses direct observation and interviews with parents. The results of the study show that children aged 7-8 years show significant development in various aspects. Cognitive development is seen from children’s ability to solve problems and think logically. Children’s emotional development is seen from their ability to manage emotions and interact with the surrounding environment. Children’s spiritual development is seen from their understanding and practice of religious values in everyday life. Children’s motor development is seen from their physical abilities and movement coordination. This study provides an overview of the development of children aged 7-8 years and can be a reference for parents and educators in supporting children’s development